Implementation of halal food management system in small and medium enterprises food manufacturers - Ahmad, Anis Najiha (2018)
Non-compliant cases toward a Halal standard (MS1500:2009) can have negative effects on Muslim consumer confidence, as well as affecting the profitability and reputation of the companies involved. In practice, non-compliance is directly associated with ineffective implementation of the management system. This signifying the need to identify and examine the critical factors for effective implementation of Halal food management system. Additionally, although there have been calls and efforts to develop an instrument to assess the effectiveness of food management system (i.e. food safety and quality) implementation, to date, limited instrument is available for Halal context. Empirical research on the Halal food management system itself is rather lacking. To fill the practical and theoretical knowledge, the main purpose of this study is to develop an instrument that assesses the effectiveness of Halal food management system implementation for small and medium enterprises (SMEs) food companies. A mixed-methods sequential approach was employed. In the qualitative phase, 15 semi-structured interviews were conducted with Halal executives (n=7), consultants (n=4) and auditors (n=4) from JAKIM to identify critical factors for effective implementation of Halal food management system in SMEs. Two of the Halal executives are from large companies, their perspectives were obtained for benchmarking purpose. Ten themes were found; top management commitment; consumer focus; employee attributes and management; teamwork; information capacity; training and education; policy and procedures; adequate support; Halal personnel empowerment and supplier management. In the second phase, these qualitative findings were used in instrument development. In the third phase, a survey was conducted with SMEs food representative (n=181) to test and validate the developed instrument; 163 responses were used in the final analysis. Exploratory factor analysis (EFA) extracted nine factors: management and environmental support; consumer focus; employee attributes and management; teamwork; information capacity; training, policy and procedure; Halal personnel empowerment; supplier management and supplier assessment. Each factor has acceptable internal reliability (Cronbach alpha = 0.927-0.962). Confirmatory factor analysis (CFA) results provided evidence for convergent (Overall factor loading>0.7, AVE>0.5, CR>0.7) and discriminant validity (HTMT ratio<0.90). The result of structural equation modelling (SEM) found the proposed instrument to be predictive of operational performance (R2 = 0.757; Q2 = 0.475) and product quality (R2 = 0.706; Q2 = 0.564). These results indicate that the instrument developed is a valid and reliable. It can be used by a food company as a self-assessment tool. In doing so, the company may select suitable strategies to allocate their resources, provide necessary support, and increase the effectiveness of their Halal food management system. Policy makers could use these findings to formulate policies and effectively improve the components of national Halal food control system to facilitate SMEs to effectively implement their Halal food management system. As one of few studies that focus on the Halal food management system, this study constitutes a foundation that could facilitates a number of new research avenues to be explored in the future.